PENGARUH INTELLECTUAL CAPITAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING (Studi Kasus Perusahaan Sub Sektor Otomotif dan Komponennya yang Terdaftar di BEI Tahun 2016-2020) - ATIK HIDAYATI; DWI ERMAYANTI SUSILO (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This study aims to determine the effect of intellectual capital and capital structure on financial performance with competitive advantage as an intervening variable. The sample of this research is the automotive sub-sector companies and their components listed on the Indonesia Stock Exchange in 2016-2020 using purposive sampling method and based on the criteria determined by the researcher, so that the results obtained are 12 companies for 5 years. So that in the study obtained as many as 60 data. The data of this study were obtained from the annual financial statements. The analytical method used is multiple linear regression analysis and mediation analysis using the Sobel test with the help of the Statistical Product and Services Solution (SPSS) version 20 application. The results of this study indicate that intellectual capital and competitive advantage have no effect on financial performance. Capital structure has a negative effect on financial performance and competitive advantage. Competitive advantage is able to mediate the relationship between intellectual capital and capital structure on financial performance